Attempted Criminal Acts in Islamic Criminal Law - Dini Ramadhani; Nabila Az'zahra (Jurnal Sahabat ISNU SU, 2024)
In this paper, the author will discuss attempted criminal acts in Islamic criminal law. Islamic Criminal Law is an important part of the Islamic legal system that aims to maintain order, justice, and the welfare of the community. In practice, Islamic criminal law not only regulates actions that have been committed, but also addresses actions that are still in the attempted stage. An attempted criminal act is the incomplete completion of a criminal act due to several external factors, the perpetrator having intent and the initiation of the criminal act. An attempted criminal act also has several elements. For an act to be considered an attempted criminal act, it must fulfill three main elements: an act that has begun with intent, there is implementation to carry out an act, and the incompleteness of the act that is not due to the individual's own will. Regarding this attempted criminal act, there are also several opinions from scholars. Scholars, including the imams of the madhhab, do not discuss this attempted criminal act explicitly and specifically. However, this does not mean that attempted criminal acts are considered an unimportant issue, but rather because attempted criminal acts are included in the category of ta'zir crimes, which are flexible and left to the judge's discretion.Indonesia in this section.